The Philosophy Basis Of Educational Technology - Ayu Mustika; Jamaris Jamna (CV. AFDIFAL MAJU BERKAH, 2021)
Philosophy is a general theory of education. In other words, it can be deemed as a very important basis for how education is carried out, so that the goals of education are fully achieved. This is the background why an educational technology science has a philosophical foundation. Educational technology as a scientific discipline has a philosophical foundation that can be studied on educational technology that meets three philosophical studies, which are ontology, epistemology, and axiology. Based on insights retrieved from this article, it is stated that the philosophical foundation of educational technology concerning its ontology is a field of scientific study. Meanwhile, if we look at the etymology of educational technology, it is an approach used in a science. When it is viewed from an axiological point of view, educational technology emphasizes on its benefits, both in general and in particular, directly, physically and abstractly.